Program Screening Hipertensi Lansia dan Senam Hipertensi di Banyumanik Semarang Upaya Peningkatan Kesadaran Kesehatan Masyarakat di Kalangan Lansia - Sukma Afrida Putri; Rifvanda irza; Laura Khattrine Noviyanti; Merly Annawati; Sri Puguh Kristyawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is a major public health issue, especially among the elderly, due to its potential to lead to serious cardiovascular diseases such as stroke, heart attack, and kidney failure. Despite the high incidence of hypertension in the elderly population, many individuals remain unaware of the importance of managing the condition through lifestyle changes, including regular exercise. This community outreach program in RW 5 Banyumanik was designed to address these gaps by educating elderly individuals about hypertension and providing them with practical tools to manage the condition, particularly through hypertension exercises. The four stages of the program were carefully structured to ensure effective delivery and long-term impact. First, the socialization stage aimed to engage the community and raise awareness about the program's objectives. This was followed by educational sessions where participants learned about hypertension, including its causes, risks, and prevention strategies. The elderly were also introduced to specific hypertension exercises, which are designed to help control blood pressure by improving cardiovascular health and reducing stress. During the application stage, participants practiced these exercises under the supervision of trained health professionals, ensuring that they performed them correctly and safely. The final stage of the program involved monitoring and evaluation, where the participants’ understanding of hypertension and their ability to perform the exercises were assessed. Additionally, the program emphasized basic life support and first aid training, which proved beneficial in enhancing the elderly’s confidence in managing emergencies.Overall, the program was successful in improving the participants' knowledge of hypertension and empowering them with the tools to manage their health. The positive outcomes of this program highlight the importance of community-based health education and physical activity interventions in promoting healthier lifestyles for the elderly.